DAMPAK PENDIDIKAN KARAKTER DALAM MEMBENTUK KEPRIBADIAN SISWA SDN GOLO GONGGO KABUPATEN MANGGARAI, FLORES, NTT - Dafrosa Saina Niat; Ismail Nasar; Fransiskus Laka Lazar (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2019)
Character education done in school has an impact/effect on forming students’ personality. Schools or any formal educational institutions are responsible for educating, forming, and planting character values on students by using the various methods, media either in classroom through teaching process or outer classroom through extracurricular activities. This paper aims to explore and describe the implementation of character education and the impact/effect on forming students’ personality in SDN Golo Gonggo. To achieve this goal, the authors conducted literature study and qualitative research method. Research data are collected by using observation, interview, and documentation method. The result of this research showed that, the implementation of the character education in building character education was conducted through three kinds of designes, such us: the culture of school, teaching-learning activity and extracurriculer program. The implementation of character education was done appropriate to the rues of school and the schedule that have been determined by the school. The effect of character education in forming the students’ personality of SDN Golo Gonggo were : (1). Students were be able for being polite and respectful for the olders. (2). Students have motivation and enthusiasm to continue learning and heaving good achievement. (3). Students have willingness and having enthusiasm in developing the proclivity and tallent. (4). Students were be able and creating and interaction with other people. (5). Students have good personality and having good physical appearance.